The "Green-Direct" Transformation at PT. Distributor Logistik Nusantara (DLN) : Facing Inertia in the Era of Sustainability - Ambarwati, Endah; Nandini Urifianto, Yunia; Sidharta, Arif; Indriana, Nadya; Zazuli, Ahmad (Hut Publication Business and Management, 2025)
The development of the consumer goods distribution industry in the last five years has been marked by the acceleration of digital transformation and increasing demands for environmental sustainability. This condition has encouraged legacy distribution companies to implement two change agendas simultaneously: supply chain digitalization and the implementation of green logistics (twin transformation). However, the implementation of these changes often triggers internal resistance. This study aims to analyze the psychological, structural, and organizational cultural factors that trigger resistance from area managers and senior operational employees to the Green-Direct project at PT. Distribusi Logistik Nusantara, particularly in the unfreezing phase of Lewin's Change Model, and to formulate change strategies in the movement and refreezing phases. This study uses a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and analysis of internal company documents, then analyzed using Lewin's Change Model framework. The results of the study indicate that resistance is multidimensional and develops systemically since the unfreezing phase, triggered by threats to professional identity, shifts in operational control structures, and the strength of the legacy organizational culture. This resistance is not static and can be reduced through a participatory approach in the movement phase, and begins to be internalized sustainably when digitalization and green logistics are institutionalized into SOPs, performance indicators, and reward systems in the refreezing phase. This study confirms the relevance of Lewin's Change Model in explaining the dynamics of twin transformation in legacy distribution companies and emphasizes the importance of managing resistance as a social and cultural process, not merely a technological issue.